Drive to Greener Future: Tribological and Engine Performances of Nano-Oil - Abdollah, Mohd Fadzli bin; Abdullah, Muhammad Ilman Hakimi Chua; Amiruddin, Hilmi; tamaldin, noreffendy; Mat Nuri, Nur Rashid (2014)
This paper presents the experimental study on the tribological and engine performances of nano-oil. In this study, the nano-oil was prepared by dispersing an optimal composition (0.5 vol.%) of 70nm hexagonal boron nitride (hBN) nanoparticles in conventional diesel engine oil by sonication technique. The tribological study was performed using a four-ball tribometer, while the single cylinder diesel engine performance test was conducted using 20 hp, air cooled type, eddy current dynamometer. By comparing with conventional diesel engine oil, it was found that the nano-oil is effective in reducing the coefficient of friction and enhancing the engine performance, simultaneously reduces frictional wear on the contact surfaces of engine components. The results presented here may facilitate improvements in the energy efficiency of tribological systems towards a sustainable future for green technology advancement.